BIOACTIVITY OF Anvillea radiata COSS & DUR. COLLECTED FROM THE SOUTHEAST OF MOROCCO - Mohamed, Bammou; Khalid, Sellam; Lhoussaine, El Rhaffari; Tariq, Bouhlali Eimad Dine; Amine, Daoudi; Jamal, Ibijbijen; Laila, Nassiri (European Scientific Journal, ESJ, 2015)
The in vitro antimicrobial and antioxidant activities of aqueous, methanolic and ethyl acetate extracts of Anvillea radiata (Asteraceae) were investigated. Antibacterial activity was tested against six pathogenic strains viz. Staphylococcus aureus (ATCC 29213), Staphylococcus aureus (ATCC 6538), Bacillus subtilis (ATCC 6633), Salmonella abony (NCTC 6017), Escherichia coli (ATCC 25922), Escherichia coli (ATCC 8739) and by using Disc diffusion method and Minimum Inhibitory Concentrations (MIC). Total antioxidant capacities were assessed by DPPH (1.1 diphenyl-2- picrylhydrazyl) radical scavenging activity, ferric reducing power (FRAP) and ABTS (2.2’-Azinobis-(3-ethylbenzothiazoline-6-sulfonic acid)) radical cation scavenging activity. Total phenolic contents were measured by Folin- Ciocalteu assay. Among the extracts tested, methanolic extract showed promising antibacterial activity against bacteria and reasonable antioxidant properties, and they can therefore be potentially used as a natural additive in food, cosmetic and pharmaceutical industries.